2020
DOI: 10.17645/mac.v8i1.2444
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ethos and Pathos in Scientific Truth Claims in Public Discourse

Abstract: The article seeks to explore the role played by the rhetorical modes of ethos and pathos when scientific knowledge is constructed in public discourse. A case study is presented on the public debate in Germany on possible risks to bees from neonicotinoid pesticides, focusing especially on a detailed analysis of scientific knowledge claims found in texts produced by two lobbying groups involved. The findings indicate distinctive rhetorical patterns in the context of scientific truth claims realising, for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Similar results are revealed by Simon's (2020) linguistic analysis of different knowledge claims of possible risks of neonicotinoid pesticides, which are published in documents by the agricultural industry compared to environmental organisations. The author approaches emotions from a rhetorical perspective by distinguishing between ethos (measured as trustworthiness: expertise, integrity, and benevolence) and pathos.…”
Section: Emotional(ised) Contentsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar results are revealed by Simon's (2020) linguistic analysis of different knowledge claims of possible risks of neonicotinoid pesticides, which are published in documents by the agricultural industry compared to environmental organisations. The author approaches emotions from a rhetorical perspective by distinguishing between ethos (measured as trustworthiness: expertise, integrity, and benevolence) and pathos.…”
Section: Emotional(ised) Contentsupporting
confidence: 73%
“…• EmoƟonal messages and • scienƟfic storytelling (Lidskog, Berg, Gustafsson, & Löfmarck, 2020) • EmoƟons in NGO-and • industry documents (Simon, 2020) • EmoƟons in science • media coverage (Huber & Aichberger, 2020) • EmoƟons towards • science/scienƟsts (Humm, Schrögel, & Leßmöllmann, 2020) • EmoƟons as moƟve (Niemann, BiƩner, Schrögel, & Hauser, 2020) • EmoƟons during and • aŌer recepƟon (Reif, Kneisel, Schäfer, & Taddicken, 2020;Schneiders, 2020;Taddicken & Wolff, 2020) Janich ( 2020 What feels good is valuable and worth striving for (see also Pham, 2007). In addition, because individuals know that their emotions are strongly correlated with their values, they assume this is also the case with other people (Bromme & Gierth, in press).…”
Section: Emoɵons Of Science Communicaɵon Audiences Emoɵonal(ised) Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphors are also powerful rhetorical devices that can be used to support three classical strategies of persuasion: the appeal to logical arguments ( logos ), the appeal to emotions ( patho s), and appeals to the good character of the speaker and the shared values ( ethos ) ( Ferrari, 2018 ; Miyawaki, 2018 ). Appeals to emotions as well as to good character and trustworthiness are especially relevant for the studies of controversies, where opposing sides use a range of discursive tools to legitimize or de-legitimize a particular cause ( Simon, 2020 ).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…For instance, the phrase "flatten the curve, " meaning the reduction of the statistical count of infections and death by COVID-19, has been used as "a rhetorical anchor for communicating the risk of viral spread" (Amidon et al, 2021). Other rhetorical studies suggested that the elements of ethos and pathos have a prominent function when the science that is being communicated is associated with risk (Miller, 2003;Simon, 2020) or public contestation (Martini, 2018).…”
Section: Methodsmentioning
confidence: 99%